Optimising ballistic facial coverage from military fragmenting munitions: a consensus statement. Issue 2 (February 2017) - Breeze, J.; Tong, D.C.; Powers, D.; Martin, N.A.; Monaghan, A.M.; Evriviades, D.; Combes, J.; Lawton, G.; Taylor, C.; Kay, A.; Baden, J.; Reed, B.; et al.
Abstract: VIRTUS is the first United Kingdom (UK) military personal armour system to provide components that are capable of protecting the whole face from low velocity ballistic projectiles. Protection is modular, using a helmet worn with ballistic eyewear, a visor, and a mandibular guard. When all four components are worn together the face is completely covered, but the heat, discomfort, and weight may not be optimal in all types of combat. We organized a Delphi consensus group analysis with 29 military consultant surgeons from the UK, United States, Canada, Australia, and New Zealand to identify a potential hierarchy of functional facial units in order of importance that require protection. We identified the causes of those facial injuries that are hardest to reconstruct, and the most effective combinations of facial protection. Protection is required from both penetrating projectiles and burns. There was strong consensus that blunt injury to the facial skeleton was currently not a military priority. Functional units that should be prioritised are eyes and eyelids, followed consecutively by the nose, lips, and ears. Twenty-nine respondents felt that the visor was more important than the mandibular guard if only one piece was to be worn. Essential cover of the brain and eyes is achieved from all directions using a combination of helmet and visor. Nasal cover currently requires the mandibular guard unless the visor can be modified to cover it as well. Any such prototype would need extensive ergonomics and assessment of integration, as any changes would have to be acceptable to the people who wear them in the long term.